Employing visual thinking skills in the techniques of advertising art - Bydaa Sabih Al-Gharawi (Journal of Techniques)
The current research attempts to look into the modern trends in artistic education and teaching methods to upgrade some cultures of teaching art according to scientific methodology. It also works on enhancing current education methods to reach excellence in the process of teaching advertisement art techniques, where the research aims to take on skills of visual thinking and adopt them in preparing teaching units that represent weekly lectures for the students of the Department of Printing Design Techniques / First Grade, and develop their abilities in translating visual language carried in advertisements to a written phonic language that requires training on visual thinking skills. Therefore the zero assumption placed that there are no differences of statistic indication at level of indication of (0.05) between the average of degrees of trial group students and the control group in visual thinking test. As for the second chapter, it contained the theoretical frame that discusses two axes: Visual thinking and advertising. Actions came in third chapter where it contained research society and its sample and the research tool prepared by researcher as a test of visual thinking at the end of experiment. The fourth chapter reviews the results which showed that using visual thinking as a method to teach the subject of advertisement art techniques helped the learners understanding and active positive learning through the faster reaching of thoughts and information than the common method. The conclusions showed that there is a positive relation of statistical indication between visual thinking skills and teaching the subject of advertisement art techniques in a balanced form which helped on boosting concept abilities in the way that fits with art learner. The recommendations included: Adopting visual thinking skills in teaching subjects of design mark in different departments of Applied Arts Institute.